Morphometric changes in the heart of rats with alloxan and streptozotocin diabetes - Saule Zhautikova; Kulash Nurseitova; Lyubov Piven; Tatyana Kim; Irina Baryshnikova; Gulnur Bakaramova; Arailym Amantayeva; Zhadyra Orynbayeva (Caspian Journal of Environmental Sciences)
In diabetes mellitus (DM), the ability of the myocardium to fully relax and fill with blood during diastole is impaired. Clinical observations by various authors confirm the presence of myocardial hypertrophy in patients with diabetes; in particular, an increase in the thickness of its posterior wall and interventricular septum has been established. In this regard, of undoubted interest is the study of the relationships between the frequency, structure, and severity of pathogenetic morphometric disorders of the heart in animals with experimental models of alloxan and streptozotocin diabetes. This study aimed to study morphometric changes in the heart in animals at different stages of development using models of experimental alloxan and streptozotocin diabetes. In this study, 450 rats with experimental diabetes were studied (intravenous administration of alloxan 35 mg kg-1): Model 1:  alloxan diabetes (group A): divided into subgroups: A1: 6 months of observation (50 animals in each subgroup); A2: 12 months; A3: 24 months; Model 2: streptozotocin diabetes (group C): C1: 6 months; C2: 12 months; C3: 24 months. CI: control group of intact rats: CI1: 6 months (30 individuals per subgroup); CI2: 12 months; KI3: 24 months. They received a single injection of sterile saline solution into the femoral vein. Morphometric studies, volumetric ratios of tissue components were determined using an ocular measuring grid for cytohistostereometric studies. Avtandilova Statistical methods were used for studying the significance of the linear correlation coefficient (Pearson) and the rank coefficient (Spearman), then checked based on Student's t-test. In this study, upon extraction, the animal's heart was processed, dried, and weighed on a torsion balance. Weight in animals KI1 heart weight was 3.5 g with a total weight of 195.4 g. In animals with intravenous administration of alloxan, the heart weight (p < 0.05) was in the range of 3.7-3.9 g with a total weight of 194.4 -195.7 g in streptozotocin diabetes, the weight of rats heart (p < 0.05) was 4.0-4.1 g with a total weight of 193.2-193.5 g. In a morphometric study of experimental animals' right and left ventricles and pulmonary arteries, the indicators were higher in group A3. The volume of right ventricle in alloxan-induced diabetes was significantly (p < 0.05) greater than in the control groups. In the case of morphometric indicators of the rats heart with streptozotocin diabetes, pronounced ultrastructural changes distinguished cardiomyocytes. Lysis of cristae and outer mitochondrial membranes with the formation of myelin figures and dense protein bodies, were observed for alloxan diabetes at 24 months. Processes of hypertrophy of cardiomyocytes prevailed; nuclei volume increased (p < 0.05) by 34.6%, and euchromatin content and mitochondria increased by 23.8%.